An unusual case of arteriovenous fistula-related venous hypertension: sonographic detection of a culprit perforating vein with movie and compact review. Issue 1 (December 2016) - Kamata, Tadashi; Yamamoto, Kojiro; Okamura, Motohiro; Iehara, Noriyuki
Abstract Background Venous hypertension is one of the critical complications of arteriovenous fistula (AV fistula). Here, we report an unusual variation of venous hypertension which was caused by retrograde outflow through a perforating vein of the elbow. Case presentation A 79-year-old man with diabetic nephropathy had an AV fistula created at his left proximal forearm 2 years before referral. Shortly after the creation of the AV fistula, he developed swelling of the left hand and forearm. Six months prior to the referral, persistent pain of the left hand developed, and he visited the nephrology unit. An anastomosis of the AV fistula was located 5 cm distal to the elbow. Inspection, palpation, and auscultation did not suggest outflow stenosis. Ultrasound showed mature upper arm venous outflow without stenosis. His proximal radial artery had been anastomosed side-to-end to a nearby proximal forearm superficial vein. Color Doppler analysis revealed a retrograde outflow through an antecubital perforating vein, which drained into the deep portion of the forearm and then disappeared. Superficial veins of the left forearm had been exhausted due to a previous attempt to create a wrist AV fistula. Given the above, it was suspected that the unusual retrograde outflow through the perforating vein caused venous hypertension by interfering with the venous return of the forearm, which had been dependent on deep veins. The patient subsequently underwent ligation of the perforating vein. The day after the operation, the pain disappeared and swelling improved. The dialysis treatments were continued without problems. Conclusions Retrograde outflow through a perforating vein can be a cause of venous hypertension in a patient with an AV fistula created using the proximal radial artery. Close sonographic examination of antecubital vessels should be done if a practitioner encounters unilateral whole forearm edema without apparent proximal outflow stenosis.